SYSTEMATIC LITERATURE REVIEW: PEMBELAJARAN SUDUT MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK - Adha, Idul; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Somakim, Somakim (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2023)
This research aims to conduct a literary review regarding corner learning using Indonesian Realistic Mathematics Education (PMRI). The method used is Systematic Literature Review (SLR). The data in this research is information on learning angles using (PMRI) taken from selected articles. The articles used as data sources in this research are 6 articles with the criteria being (1) the content being taught is about angles, (2) using the PMRI approach, (3) using the design research method, (4) the articles come from reputable and indexed journals. Sinta and Scopus. Based on the results of the study, it was found that (1) the initial problem in the research was students' misconceptions about the concept of angles, (2) the use of the PMRI context can bridge students in understanding the context of angles, (3) learning activities produce local instructional theory (LIT), (4) research results state that learning becomes more meaningful because students learn from real situations.